Analysis of Possible Reductions of Rejects in Battery Cell Production during Switch‐On and Operating Processes. Issue 7 (7th May 2021) - Kehrer, Mario; Locke, Marc; Offermanns, Christian; Heimes, Heiner; Kampker, Achim
Abstract : Battery cell production is one of the key industries for electric mobility. To become more competitive and economic, battery cell production requires maximum efficiency in every process step. An efficient production can be achieved by a low rejection rate during switch‐on and operating processes. For all process steps of battery cell production relative rejection rates and absolute scrap amounts are analyzed. Herein, it is aimed to find out to what extent existing quality inspection systems can eliminate battery cell production rejects, whether there are deficits in their application and if approaches of Industry 4.0 can offer solutions. The results are that coating is the process step with the highest reject and data‐driven methods are suitable tools to reduce the rejection rate in the production of current and future battery cells. Abstract : Herein, the reject rates are analyzed in the battery cell production process and both the technical and economic relevances are evaluated. A detailed study is conducted to analyze the reject rates in every production process step. For the reject reduction data acquisition methods are evaluated and the relevance of switch‐on processes in small‐scale production is identified.